Identifikasi Jenis Tumbuhan Tingkat Tinggi Angiospermae di Sungai Jatimalang, Kabupaten Sukoharjo, Jawa Tengah - Viky Sabela Dewi Fortuna; Ananda Tri Hapsari; Desrini Prapti Pratiwi; Mentari Suri Insani; Rahma Isnaini Puji Astuti; Murni Ramli (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
Biodiversity is a crucial element in ecosystems and human life. The Jatimalang River in Sukoharjo Regency, Central Java, is an ecosystem rich in biodiversity, particularly within the Angiospermae plant group. This study aims to identify the species of Angiospermae along the Jatimalang River and analyze their distribution based on environmental conditions. The results show the diversity of Angiospermae species from various families, including Poaceae, Musaceae, Fabaceae, and Euphorbiaceae, which demonstrate complex ecological adaptations to local conditions. This study is expected to contribute to conservation efforts and natural resource management in the region. By prioritizing the protection of important habitats and conducting further research, the Jatimalang River area can continue to support ecosystem sustainability and the welfare of the communities dependent on it.